MUNICIPAL BOND AS A SUPPORTING TOOL OF REGIONAL ECONOMIC DEVELOPMENT IN POLAND - Sylwester Kozak (Polityki Europejskie, Finanse i Marketing)
The paper examines the use of municipal bonds in funding development activities of local governments in Poland. The research is based on the data from Ministry of Finance, ECB, Central Statistical Office and the platform CATALYST. The analysis indicates that in Poland the level of bonds` usage by municipalities is lower than the EU average. Poland`s entrance to the EU and the EU structural funds significantly increased the interest of municipalities in funding investments with bonds, especially in 2008-2010. Significant portion of municipal bonds was dedicated to the regional development projects, mostly in infrastructure. In the years 2011-2014 the advantageous features of bonds caused an increase in the value of outstanding municipal bonds, as well as their share in the total municipal debt. Revenue bonds issued by the municipal enterprises have become a new option for funding infrastructure regional projects.